Advancing Applications of Black Phosphorus and BP‐Analog Materials in Photo/Electrocatalysis through Structure Engineering and Surface Modulation. Issue 19 (6th August 2020) - Yin, Teng; Long, Liyuan; Tang, Xian; Qiu, Meng; Liang, Weiyuan; Cao, Rui; Zhang, Qizhen; Wang, Dunhui; Zhang, Han
Abstract: Black phosphorus (BP), an emerging 2D material semiconductor material, exhibits unique properties and promising application prospects for photo/electrocatalysis. However, the applications of BP in photo/electrocatalysis are hampered by the instability as well as low catalysis efficiency. Recently, tremendous efforts have been dedicated toward modulating its intrinsic structure, electronic property, and charge separation for enhanced photo/electrocatalytic performance through structure engineering. Simultaneously, the search for new substitute materials that are BP‐analogous is ongoing. Herein, the latest theoretical and experimental progress made in the structural/surface engineering strategies and advanced applications of BP and BP‐analog materials in relation to photo/electrocatalysis are extensively explored, and a presentation of the future opportunities and challenges of the materials is included at the end. Abstract : Black phosphorus (BP) shows great potential in photo/electrocatalytic applications. The advantages, limitations, modulation mechanism, and strategies of BP and BP‐based catalysts in the photo/electrocatalysis field are profoundly elucidated. Further, newly emerged BP‐analog materials are summarized and future directions for BP and BP‐analog materials in this field are provided.